Leishmania flagellum attachment zone is critical for flagellar pocket shape, development in the sand fly, and pathogenicity in the host - Sunter, Jack D; Yanase, Ryuji; Wang, Ziyin; Catta-Preta, Carolina Moura Costa; Moreira-Leite, Flavia; Myskova, Jitka; Pruzinova, Katerina; Volf, Petr; Mottram, Jeremy C; Gull, Keith (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Leishmania kinetoplastid parasites infect millions of people worldwide and have a distinct cellular architecture depending on location in the host or vector and specific pathogenicity functions. An invagination of the cell body membrane at the base of the flagellum, the flagellar pocket (FP), is an iconic kinetoplastid feature, and is central to processes that are critical for Leishmania pathogenicity. The Leishmania FP has a bulbous region posterior to the FP collar and a distal neck region where the FP membrane surrounds the flagellum more closely. The flagellum is attached to one side of the FP neck by the short flagellum attachment zone (FAZ). We addressed whether targeting the FAZ affects FP shape and its function as a platform for host-parasite interactions. Deletion of the FAZ protein, FAZ5, clearly altered FP architecture and had a modest effect in endocytosis but did not compromise cell proliferation in culture. However, FAZ5 deletion had a dramatic impact in vivo: Mutants were unable to develop late-stage infections in sand flies, and parasite burdens in mice were reduced by >97%. Our work demonstrates the importance of the FAZ for FP function and architecture. Moreover, we show that deletion of a single FAZ protein can have a large impact on parasite development and pathogenicity.
Keywords: interakce hostitele a parazita; morphogenesis; zvířata; Cell Membrane; Intercellular Junctions; Host-Parasite Interactions; endocytóza; buněčná membrána; myši; Flagella; Mice; Protozoan Proteins; Leishmania; flagella; delece genu; Psychodidae; Cilia; Gene Deletion; pathogenicity; Animals; mezibuněčné spoje; virulence; cilie; flagellar pocket; Endocytosis; Virulence; protozoální proteiny